Organization Justice and Turnover Intention: The Mediating Role of Job Satisfaction in Commercial Banks - Chaudhary, Bhagwati Pd.; Pun, Ramba Darlami (The Lumbini Journal of Business and Economics, 2021)
The study intends to investigate the mediating effect of job satisfaction on the relationship between Organization justice and Turnover Intention. Data for the study was collected through convenience sampling technique from 221 employees of commercial banks on five points likert scale through a self administrative questionnaire. Descriptive and casual comparative research design was used to conduct the research study using correlation and hays process macro approaches. The findings of the study revealed that job satisfaction partially mediates the relationship between organization justice and Turnover Intention. In this regard, management authority of commercial banks can re-formulate their policies and strategies for their employees with regard to organization justice to minimize Turnover Intention and enhance job satisfaction.